2016
DOI: 10.1002/ppap.201500229
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Radical Species on Structural and Electronic Properties of Amorphous Carbon Films Deposited by Radical-Injection Plasma-Enhanced Chemical Vapor Deposition

Abstract: Amorphous carbon (a-C) films are deposited using a radical-injection plasma-enhanced chemical vapor deposition (RI-PECVD) system employing a mixture of H 2 and CH 4 gases. Variations in the structural and electronic properties of the resulting films with changes in the residence times of radical species and molecules are investigated by varying the total gas flow rate from 50 to 400 sccm. With decreasing residence time, the deposition rate is found to gradually increase, reaching a maximum value at a residence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 42 publications
(82 reference statements)
0
13
0
Order By: Relevance
“…The deposition of CNFs on 3DG led to an increase in D peak intensity around 1350 cm −1 which represents disorder in the previous graphene structure. Another reason for high D peak could be attributed to the fact that the deposition of VACNF was done using PECVD, which generally creates a lot of radicals that affect the quality of carbon structure produced . The first‐order G band around 1580 cm −1 , which is indicative of planar sp 2 vibrations, was seen after deposition of VACNF as well.…”
Section: Resultsmentioning
confidence: 99%
“…The deposition of CNFs on 3DG led to an increase in D peak intensity around 1350 cm −1 which represents disorder in the previous graphene structure. Another reason for high D peak could be attributed to the fact that the deposition of VACNF was done using PECVD, which generally creates a lot of radicals that affect the quality of carbon structure produced . The first‐order G band around 1580 cm −1 , which is indicative of planar sp 2 vibrations, was seen after deposition of VACNF as well.…”
Section: Resultsmentioning
confidence: 99%
“…The growth of a-C:H films was performed using a radical-injection plasma enhanced chemical vapor deposition (RI-PECVD) system, in which two plasma sources were stacked and connected through a showerhead electrode [20,21]. Figure 1 shows the schematic diagram of RI-PECVD system.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, formation of graphene layers on Ni dates back to more than 50 years where it was observed in industrial applications [21,134,135]. Ni (111) has the least lattice mismatch with graphene compared to other transition metals (< 1%) making it catalytically more favourable for growing graphene [136]. Graphene grows on Ni through bulk diffusion [21,115,118,136].…”
Section: Solid Substratesmentioning
confidence: 99%
“…Mogera et al investigated twisted multilayer graphene growth on polycrystalline Ni [136]. It was found that graphene growth on polycrystalline Ni enhances Ni (111) orientation when compared with other treatments of Ni including annealing. Figure 18 shows the difference between the interlock of the sample with and without a graphene layer.…”
Section: Solid Substratesmentioning
confidence: 99%
See 1 more Smart Citation